2015
DOI: 10.2147/ppa.s91973
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence in multiple sclerosis: a survey of Belgian neurologists

Abstract: BackgroundPoor treatment adherence is common among patients with multiple sclerosis (MS). This survey evaluated neurologists’ perception of treatment adherence among MS patients.Materials and methodsThis questionnaire-based survey of Belgian neurologists treating MS patients was conducted between June and July 2014. Face-to-face interviews with the neurologists were based on a semistructured questionnaire containing questions regarding the perception of the treatment-adherence level.ResultsA total of 41 neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Hansen et al [22] found that 30-40% of MS patients were adherent to their treatment over a period of 2 years. However, higher medication adherence rates were reported by Menzinet al among MS patients, which ranged from 41 to 88% [23].…”
Section: Discussionmentioning
confidence: 74%
“…Hansen et al [22] found that 30-40% of MS patients were adherent to their treatment over a period of 2 years. However, higher medication adherence rates were reported by Menzinet al among MS patients, which ranged from 41 to 88% [23].…”
Section: Discussionmentioning
confidence: 74%
“…However, in order to achieve the intended therapeutic effect in the form of reducing the number of relapses, slowing down the progression of the disease, and reducing disability and the number of hospitalizations, the patient must follow the treatment recommendations, such as taking the drug according to the prescribed dosage and for the complete duration of the treatment. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 It should be noted that sociodemographic factors may also significantly influence compliance; for example, people with lower economic status are characterized by lower adherence. 8 …”
Section: Introductionmentioning
confidence: 99%
“…There are many international surveys evaluating the approaches of physicians to MS patients (3,4,5). However, very few of these studies were designed to question differences associated with the level of experience of physicians.…”
Section: Discussionmentioning
confidence: 99%